DETERMINATION OF GROWTH RATES OF (100) AND (110) FACES OF SYNTHETIC GOETHITE BY SCANNING FORCE MICROSCOPY - APPLICATION TO IRON (HYDR)OXIDES - Weidler P.G.; Hug S.J.; Wetche T.P.; Hiemstra T. (My University, 1998)
For the first time, the growth rate of the (100) and (110) faces of goethite has been measured in situ with scanning force microscopy. Submicron sized goethite particles were immersed in aerated aqueous Fe(II)solutions, whereby Fe(III) was formed by oxidation of Fe(II) by oxygen. Oxidation of Fe(II) is an important and ubiquitous geochemical process in soils and sediments exposed to changing redox conditions. The SFM measurements confirmed that Fe(II) oxidation is catalyzed by goethite and showed that Fe(III) is incorporated on the existing crystal faces. The growth velocity of the (100) face exceeded the one of the (110) faces by about a factor of 1.5 at the experimental conditions of this study (10 mM FeSO4 and KCl, 5mM acetate, pH 5). The different growth rates result in a predominance of (110) faces, which is also observed when goethite is formed in oversaturated Fe(III) solutions at pH 9, and explains the generally observed morphology of goethite particles. The growth behavior appears to be reaction controlled rather than transport controlled. The preferential growth on the (100) faces could be driven by steric factors, in that the grooves on the (100) faces formed by rows of missing oxygens provide preferred sites for Fe incorporation. The surface properties on the different crystal faces are discussed in the frame of CD-MUSIC model.